Educazione, cittadinanza, volontariato Frontiere pedagogiche - Pieri, Giulia (Premio Ricerca «Città di Firenze», 2013)
In a complex, global, multicultural and post-modern society such as the contemporary one, the concepts of "democracy", citizenship "and" training" are undergoing a more urgent and necessary rethinking, which is tracing more and more constant new variations, contaminations and interconnections. On the one hand citizenship has become today active and participatory, as today it can be exercised. On the other hand, volunteering can be a response to the need for participation claimed by contemporary societies: the donation of blood, a particular declination of the traditional concept of gift, is seen as an opportunity to participate in community life and to exercise active and responsible citizenship. From this point of view, the subject is the main actor and protagonist of contemporary processes, and must be trained in understanding the complexity of the notion of citizenship.